2013
DOI: 10.1097/iae.0b013e318295f758
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitreoretinal Surgery in Maximizing Treatment Outcome Following Complications After Proton Therapy for Uveal Melanoma

Abstract: Vitreoretinal surgery was efficient in maximizing treatment outcome after proton therapy, as it allowed a better oncologic follow-up. Pars plana vitrectomy permitted panretinal photocoagulation to avoid neovascular glaucoma or retinal detachment repair. Macular surgery improved visual acuity, especially in anterior melanoma, whereas repeated surgery may increase the risk of enucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In our series, we had 1 case of early detachment (0.9%) following PBT, a round hole away from the tumour site, with a similarly low rate of 2 from 1005 eyes (0.2%) reported by Tran et al 7 Of those in the Tran series, one was a rhegmatogenous detachment, and the other a serous detachment associated with vitreous haemorrhage. The timing of vitrectomy was not specified.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In our series, we had 1 case of early detachment (0.9%) following PBT, a round hole away from the tumour site, with a similarly low rate of 2 from 1005 eyes (0.2%) reported by Tran et al 7 Of those in the Tran series, one was a rhegmatogenous detachment, and the other a serous detachment associated with vitreous haemorrhage. The timing of vitrectomy was not specified.…”
Section: Discussionmentioning
confidence: 84%
“…6,7,11 In these cases, the extent of vitreoretinal adhesions seems to be critical, and as these adhesions tend to progress over time early retinal detachment repair is theoretically preferable and may be associated with better visual outcomes. 5,7,11 In addition to retinal detachments due to vitreoretinal traction, other mechanisms such as proliferative vitreoretinopathy, 5 poor adhesion between the retina and sclera at the site of surgical coloboma, 5 and edge recurrence are described. 15 A single case of intraocular dissemination of melanoma cells had been reported by Foster et al 10 54 months following vitrectomy in an irradiated uveal melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that laser photocoagulation helps to prevent neovascular glaucoma [21]. In their study, Missotten et al [22 ]found significantly elevated aqueous VEGF levels in eyes with uveal melanoma irrespective of the treatment compared with controls and eyes with a retinal detachment alone.…”
Section: Discussionmentioning
confidence: 98%
“…Vitrectomy after proton beam therapy is a safe procedure, and vitrectomy facilitates tumor surveillance through reestablishing transparency of the visual axis. Furthermore, vitrectomy increases the chances of eye retention as it allows both panretinal photocoagulation to avoid neovascular glaucoma and surgical repair of a rhegmatogenous detachment [21]. Therefore, even when functional outcome is limited, performing vitrectomy is justified.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical effectiveness of proton radiotherapy (local control) can be improved by ensuring possible endoresection of the remaining part of the tumour [ 42 ]. This helps improve the outcome of treatment while at the same time preserving the eyeball.…”
Section: Discussionmentioning
confidence: 99%